Tai Chi Intervention in Osteoporosis: An Overview of Systematic Reviews and Meta-Analyses - BAI, Bihui; YAO, Fei; XIE, Fangfang; Yue, Hongyu; Cui, Jiahe; ZOU, Hanyu; Ma, Jianwen; XIE, Chaoqun; Jiang, Zaifeng (The Journal of the International Society of Chinese Health Practices, 2025)
Abstract: Objective: This study aimed to analyze the evidence from systematic reviews/meta-analyses on Tai Chi intervention for osteoporosis and discuss the quality of evidence regarding Tai Chi intervention for osteoporosis. Methods: We searched databases including CNKI, Wanfang, VIP, SinoMed, PubMed, Web of Science, Embase, and Cochrane Library for systematic reviews/meta-analyses on Tai Chi intervention for osteoporosis published up to September 30, 2024. The AMSTAR2 checklist was used to evaluate the methodological quality of included studies, and an evidence map was created to synthesize interventions. Results: Based on the assessment using the AMSTAR2 checklist, 26 studies were finally selected, with 4 of high quality, 11 of moderate quality, 8 of low quality, and 3 of very low quality. The evidence map showed that the effect of Tai Chi on osteoporosis was significant, with 4 studies showing comparable efficacy and superiority, and 22 studies showing comparable efficacy and inferiority. Conclusion: High-quality evidence for the intervention of Tai Chi in osteoporosis prevention and treatment is relatively scarce, and the quality remains at a moderate and low level. More attention should be paid to methodological design in clinical studies, and more large-sample, multicenter randomized controlled trials should be conducted to improve research quality and provide higher-level evidence-based medical evidence. This will help confirm the value of Tai Chi in the prevention and treatment of osteoporosis and promote its application in clinical practice.